Taxonomy Of Operational Risks inFintech: A Systematic Literature Review (2023)
Objective: The Fintech industry has been gaining importance among customers of the financial system, thanks to the agility, scope, and simplicity of the services offered through digital platforms. This article aims to describe, from the literature, the Fintech taxonomy to identify the Operational Risks by mapping current knowledge and finding gaps in the relevant literature.Design/Methodology/Approach: A systematic literature review is carried out based on a bibliometric analysis using the search equation "Fintech", "Risk", "Credit" in the SCOPUS indexer. Eighty scientific articles were obtained, and a .cvs database was downloaded to perform the cooccurrence study of keywords with the VOSviewer® software. Subsequently, a content analysis was performed by the ATLAS.ti® tool.Results/Discussion: The review proposes a taxonomy of five codes from the point of view of different authors: Cyber Risk, Model Risk, Business Practices Risk, Customer Knowledge Risk, and Data Protection Risk. They help to identify the classification of Fintech risks for analysis.Conclusions: The analysis is carried out by dispersion diagrams, which show the degree of relationship between the different risk variables in Fintech.Originality/Value: This document maps the information and scientific knowledge related to the classification of Operational Risks in Fintech, their degree of relationship, and consequences.Keywords:Fintech; Financial Risks; Operational Risk; Systematic Literature Review; Taxonomy